Towards adoption of mobile data collection for effective adaptation and climate risk management in Africa. Issue 2 (16th May 2022) - Adekola, Olalekan; Lamond, Jessica; Adelekan, Ibidun; Bhattacharya‐Mis, Namrata; Ekinya, Mboto; Bassey Eze, Eze; Ujoh, Fanan
Abstract: The collection and use of data on climate change and its impacts are crucial for effective climate adaptation and climate risk management. The revolution in internet access, technology and costs has led to a shift from using traditional paper‐based data collection to the use of Mobile Data Collection using Personal Digital Assistants (PDA) such as smartphones and tablets. In this paper, we report our experiences using both approaches for a household and business survey during a climate adaptation study in two Nigerian cities—Makurdi and Calabar. The focus of this paper is to evaluate and compare the effectiveness of using traditional paper‐based data collection and PDAs as data collection tools for climate change study in African societies. In Calabar, data were collected using paper questionnaires, while in Makurdi the questionnaires were developed on Open Data Kit (ODK) and administered using PDAs. Results show that data collection using PDA was faster, cheaper, more accurate and resulted in fewer omissions than paper‐based data collection. There was a time saving of four (4) minutes per questionnaire and a 24% cost saving when using PDA. PDA provides additional benefits where platforms can collect images, videos and coordinates. This significantly improved the credibility of the data collection process and provided further data that allowed for the mapping of environmental phenomena by linking survey research with geo‐referenced data in a geographic information systems platform to provide spatial representations of social and environmental system convergence. PDA offers a tool for collecting data that will make necessary socio‐environmental data available in a faster, reliable and cheaper manner; future research can build on this study by discovering other possible but less highlighted benefits of PDA. Although, with great benefits, there are lessons to be learnt and issues to consider when deploying PDA in large‐scale household surveys. Abstract : Little is known about the possible benefits and challenges of adopting electronic surveying for studies that require geo‐referenced data in a developing country context. To fill this gap, we report our experiences using paper‐based and electronic survey methods for a household survey during a climate adaptation study in two Nigerian cities. The paper confirmed the already known benefits of Personal Digital Assistants (PDA), in which IT offers a tool for collecting data in a faster, reliable and cheaper manner. We also found that PDA provides additional benefits for geographical studies where platforms can collect photos, videos and GPS coordinates.